Green Extraction of Six Phenolic Compounds from Rattan (Calamoideae faberii) with Deep Eutectic Solvent by Homogenate-Assisted Vacuum-Cavitation Method - Cao, Qin; Li, Junhan; Xia, Yu; Li, Wei; Luo, Sha; Ma, Chunhui; Liu, Shouxin (Molecules (Basel, Switzerland), 2018)
A homogenate-assisted vacuum-cavitation extraction (HVE) method with a “green” solvent (a deep eutectic solvent, DES) was developed to extract phenolic compounds from rattan (Calamoideae faberii). In this study, the optimum molar ratio of choline chloride (ChCl) and ethylene glycol (EG) was 1:3, the optimum volume ratio of ChCl-EG:H2O was 6:4, the solid-liquid ratio of HVE was 1:15, and the extraction time of homogenate and vacuum-cavitation were 2.0 min and 25 min, respectively. Under the optimum parameters of HVE, the extraction yield of total phenolic content with ChCl-EG solution was 6.82 mg/g. The higher total phenolic content was detected in fruit tissues (seeds 81.24 ± 1.55 mg/g, episperm 43.21 ± 0.87 mg/g, and arillus 38.47 ± 0.74 mg/g), followed by in leaves (sheath 19.5 ± 0.38 mg/g and blade 17.81 ± 0.33 mg/g). In addition, the content of specific phenolic compounds in aqueous and DES extracts was determined. Chlorogenic acid was the most abundant phenol in most organs of the rattan plant. Gallic acid was mainly distributed in the arillus; protocatechuic acid was mainly distributed in the arillus, sheath, and blade; protocatechuic aldehyde was mainly distributed in the blade, seed, and sheath; (+)-catechins were mainly distributed in the episperm, seed, and sheath; and epigallocatechin gallate was mainly distributed in the blade. The recovery rates of gallic acid, protocatechuic acid, protocatechuic aldehyde, (+)-catechins, chlorogenic acid, and epigallocatechin gallate were 93.77%, 94.09%, 97.32%, 97.83%, 94.41%, and 92.47%, respectively, by AB-8 resin.